EFEKTIVITAS PENGGUNAAN KARTU KELUARGA DALAM SISTEM ZONASI PADA PENERIMAAN PESERTA DIDIK BARU (PPDB) SMA NEGERI DI PEKANBARU - PUTRI, ANGGIE ANDIKA; Artina, Dessy; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The zoning system is a policy for accepting new students (PPDB) which iscarried out by determining the zone radius between the school and the placewhere the relevant student lives. One of the objectives of the zoning system itself ismapping students during school registration, besides aiming to equalize thequality of education, eliminate the title of favorite school, improve the quality ofteachers, and reduce the level of traffic congestion.This research was conducted using a qualitative approach, the authorwent into the field to conduct observations and direct interviews with researchinformants. The unequal quality of education equivalent to State High Schools hasbeen a problem that has been occurring for some time. Efforts made to overcomethis problem are the implementation of a zoning system for Admission of NewStudents (PPDB).The PPDB zoning system aims to: a) Ensure that the admission of newstudents is carried out in an objective, transparent, accountable, nondiscriminatory and fair manner in order to encourage increased access toeducational services, b) Ensure the availability and readiness of educational units(state schools, in particular) to be able to provide quality education services, c)Ensure equal access and fair quality of education in each zone/region determinedto be close to where students live, d) Ensure the provision of competent teachingand education staff supported by adequate infrastructure and facilities that can beprovided and used jointly by every educational unit in the designated area/zone.However, in reality, the zoning system has not been implemented wel, due to theineffective use of Family Cards. This is proven by the methods used by thecommunity to continue attending the school which has been labeled as a favoriteamong the community, including the people of Pekanbaru.The conclusion fromthe research is that equal distribution of education using the zoning system hasnot been completely successful, there are several factors causing this to happen.Suggestions from this research is to have an approach to the communityregarding the purpose of implementing a zoning system, so that the communityunderstands and complies with the regulations issued by the government.Keywords: Zoning System, Acceptance of New Students (PPDB)